Morinda citrifolia: Amino Acid and Lipid Content of the Noni Fruit at Various Stages of Maturity - Golden, K. D.; Lindsay, C. (Journal of Scientific Research, 2012)
High performance liquid chromatography (HPLC) was used to determine the amino acid and fatty acid content of Morinda citrifolia (Noni). The amino acid content both free and total was determined at the mature green, mature ripe and fermented stage of the fruit. Most of the essential amino acids were detected as free amino acids (unhydrolysed sample) at the various stages of ripening, with threonine showing the highest value (3.95±0.81 mg/100g) at the fermented stage and histidine showing the lowest value (0.05±0.02 mg/100g) at the mature green stage. The essential amino acids with the exception of tryptophan (destroyed by acid hydrolysis) were also detected as total amino acids (hydrolyzed sample) albeit at much higher concentrations. Leucine showed the highest value (94.21±18.85 mg/100g) at the mature ripe stage, whereas methionine the lowest value (2.80±1.02 mg/100g) at the mature green stage. The fatty acid content of the Noni fruit was also determined at the green, ripe and fermented stages of ripening; with the short chain caprylic acid (80.69±3.09 mg/100g) showing the highest value at the ripe stage. Significantly the essential fatty acids linolenic (8.60±0.21 mg/100g) and linoleic (50.57±0.72 mg/100g) were highest at the green stage. Also present in significant quantities were palmitic acid (44.27±0.35 mg/100g) and stearic acid (4.78±0.45 mg/100g) at the green stage. The amount of fatty acids decreased significantly at the fermented stage. Of the fatty acids detected at the fermented stage 79% of them were below 1.00 mg/100g fresh weight of the fruit. Keywords: Noni fruit; Amino acids; Fatty acids; HPLC. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.8130 J. Sci. Res. 4 (2), 467-476 (2012)